Sex offenders : identification, risk assessment, treatment, and legal issues - Saleh, Fabian M., 1965- (Oxford University Press, 2009)
This comprehensive reference by nationally recognized experts provides an interdisciplinary overview of existing knowledge about sex offenders. It provides in-depth coverage of the problem of identification, risk assessment and management, treatment, and legal solutions. It seeks to ensure public safety while at the same time maintaining medical integrity and respect for due process. The book is intended for psychiatrists, clinical psychologists, and researchers who work with sex offenders, as well as attorneys, members of the judiciary, and policymakers.